The Realization of Mood and Modality by English Conversations Video in the YouTube Channel - Anisah Puspita; Sri Wuli Fitriati; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2023)
This study discussed the language used for communication. It analyzed an English conversation video from the perspective of Systemic Functional Linguistics, especially mood and modality in interpersonal meaning. This study aimed to explain the realization of mood systems and modality in an English conversation video on a YouTube channel. In conducting this study, the researcher had several objectives to achieve. This study tried to explain the realization of mood and modality on a video of English conversations from the Learn English with Jessica channel on YouTube on YouTube by Learn English with Jessica channel. Researchers tried to explain the relationship between mood and modality in an English conversation video on a YouTube channel. The researcher used the Interpersonal meaning theory by Halliday and Matthiessen (2014). A descriptive qualitative research design was used in this study with an English conversation video on a YouTube channel taken as the subject of analysis. The results showed that the dominant mood found in this study was the declarative mood. The researcher also found the speech function in this study. Speakers often use the form of a statement to get their message across to listeners. The researcher also summarizes the modality system in which speakers mainly use probability type of modalization and inclination type of modulation to modify their conversations. This study held the function of communication as an information source, as evidenced by the interpersonal meaning they embody. They will be able to provide and receive information and advice using mood and modality